Calculating the Women’s Empowerment in Agriculture Index (WEAI) using Stata - Dione, Malick; Seymour, Greg; Ferguson, Nathaniel; Malapit, Hazel J. (SAGE Publications, 2024)
The Women’s Empowerment in Agriculture Index (WEAI) is a standardized, survey-based tool that has been widely used to track gender equality and measure empowerment, agency, and women’s inclusion in the agricultural sector (Alkire et al., 2013, World Development 52: 71–91). Since the WEAI’s release in 2012, an abbreviated version of the WEAI (A-WEAI) and a project-level version of the WEAI (pro-WEAI) have been developed (Malapit et al., 2017, The abbreviated Women’s Empowerment in Agriculture Index [A-WEAI]; Malapit et al., 2019, Development of the project-level Women’s Empowerment in Agriculture Index [pro-WEAI]). In this article, we review the shared methodology that underlies all members of the WEAI family of indices and introduce a command, weai, that can be used for index calculation. We describe the command and its options and provide empirical examples using publicly available data from the Gender, Agriculture, and Assets Project, Phase 2.